Src interacts with TRAF5 and promotes NF-κB-associated antiviral responses against iridovirus in marine teleost - Lingfeng Guan; Yi Li; Ting Yu; Jiamei Long; Runchang Zhou; Zhifeng Chen; Hua Huang; Jinglin Tan; Min Yang; Shaowen Wang; Qiwei Qin (Fish & Shellfish Immunology, 2026)

Largemouth bass virus infection subverts immune-redox homeostasis in zebrafish and is associated with coordinated suppression of NF-κB and Nrf2 signaling - Lingfeng Guan; Xinyue Zhang; Ting Yu; Yang Liu; Jiamei Long; Runchang Zhou; Hua Huang; Jinglin Tan; Zhifeng Chen; Qiwei Qin; Shaowen Wang (Fish & Shellfish Immunology, 2026)

Long-term bending performance degradation of GFRP bar-seawater sea sand concrete beams in marine environments: from material degradation to component response and bearing capacity model correction - Guanghao Mai; Zhe Xiong; Haoran Zhou; Lingfeng Zhou; Xiaohui Li; Feng Liu; Lijuan Li (Engineering Structures, 2026)

Wearable triboelectric sensor based on a single-line-contact electrode architecture for gesture recognition and human–machine interaction - Long Li; Jingyun Dai; Jiayang Lyu; Yifan Shen; Yanmin Guo; Lingfeng Du; Zhiqian Wei; Xiongtu Zhou; Yongai Zhang; Hyung-Soon Kim; Dianlun Li; Kun Wang; et al. (Chemical Engineering Journal, 2026)

Advancing analysis of biofuel precursors from lignin: complete molecular characterization using GC × GC-FID - Linyu Zhu; Miloš Auersvald; Cunhao Cui; Yuhe Liao; Jing Zhang; Qing He; Lingfeng Li; Yi Ouyang; Zhongyue Zhou; Fei Qi; Kevin M. Van Geem (Fuel, 2026)

Topology-engineered hydrogel with cellulose nanosheets for robust and high-capacity zinc-ion batteries - Wenxuan Lei; Heng Huang; Wenyu Liu; Lingfeng Zhou; Guoping Li; Pan Chen; Zu Chang; Jiangfeng Qian; Ang Lu (Carbohydrate Polymers, 2026)

Global ammonia (NH3) retrieval from the FY-3F satellite hyperspectral infrared atmospheric sounder and performance assessment - Zhili Deng; Yapeng Wang; Minqiang Zhou; Ling Gao; Lin Chen; Xifeng Cao; Lingfeng Zhang; Yuhan Jiang; Haiyang Dou; Xingying Zhang (Atmospheric Environment, 2026)

Intensive mariculture promotes molecular reorganization of dissolved organic matter in coastal waters - Kai Shen; Niangming Duan; Zhibing Jiang; Jiang Shen; Haibo Jiang; Hailong Huang; Lingfeng Zhou; Dongping Shi; Mei Li; Ying Kang; Yuanhao Wang; Xubiao Yu (Environmental Research, 2026)

A one-stone-three-birds strategy: Manipulating sodiation depth of SnTe anode enabling fast ion conduction, shuttle avoidance, and sodium replenishment for durable sodium-ion batteries - Zhiming Jia; Guoping Liu; Xu Han; Gangyong Zhou; Haihui chen; Chunjiang Jin; Ting Liu; Lingfeng Xu; Renyun Kuang; Changwang Pan; Shengping Dai; Dingwa Zhang; et al. (Chemical Engineering Journal, 2026)

Cross–Spectrum–Based Shallow Water Retrieval Using High–Resolution C–Band Miniaturized SAR Satellites - Lingfeng Zhou; Quankun Li; Liangsheng Li; Xupu Geng; Xiao-Hai Yan (Journal of Marine Science and Engineering, 2026)
Topographic and geomorphic information provides an essential basis for human development and utilization of natural resources, disaster prevention and mitigation, ecological environment protection, and scientific research. Among spaceborne remote sensing approaches, Synthetic Aperture Radar (SAR) stands out due to its ability to actively transmit and receive microwave signals, enabling high spatial coverage, all–weather, and all–day observation. With the rapid development of miniaturized satellite constellations, high–revisit and high–resolution SAR data have become more accessible, offering unprecedented opportunities for dynamic ocean observation. However, existing SAR–based bathymetry methods based on power–spectrum analysis are susceptible to sea–spike noise and 180° directional ambiguity, limiting their accuracy in shallow coastal waters. To address these limitations, a Cross–Spectrum–based Wave Ray Tracking bathymetry retrieval algorithm (CS–WRT) is developed using high–resolution imagery from mini–SAR constellations including HiSea–1 and Chaohu–1. The method incorporates cross–spectrum analysis into a localized wave ray tracking framework to effectively suppress sea–spike noise and accurately extract shallow–water wave vectors. Applied to six SAR images over the Taiwan Strait, CS–WRT consistently outperformed the power–spectrum approach in coastal environments. In the Jinjiang coastal region, comparison with Electronic Navigational Chart (ENC) data yielded a root mean square error of 2.22 m, a mean absolute percentage error of 7.06%, and a Pearson correlation coefficient of 0.84. Analysis of the shoaling slope parameter k further revealed that stronger wave shoaling effects correlate with improved retrieval accuracy, suggesting its potential as a diagnostic indicator of retrieval reliability.

Clinical efficacy and mechanistic study of intrauterine administration of E bing angong Ye for the treatment of endometritis in sows - Yi-Meng Fan; Xinyi Zhou; Lu Wang; Xiyu Wen; Xueyan Wang; Lingfeng Peng; Luyao Wang; Zhihui Hao (Theriogenology, 2026)

Computational insights of noncovalent interactions in xylan hydrate crystal - Shen Sang; Lingfeng Zhou; Jierui Ye; Pan Chen; Zhouyang Xiang (Carbohydrate Polymers, 2026)

Towards adaptive management: Future environmental risk assessment of tailing ponds in China under SSP scenarios - Junhong Ling; Bolun Zhang; Zhenxiong Zhao; Lingling Liu; Da Lv; Soon Thiam Khu; Lingfeng Zhou; Xiaoli Zhao (Journal of Environmental Management, 2026)

A refined incremental homogenization approach for heterogeneous nonlinear geomaterials without isotropization - Yongdong Li; Yuanming Lai; Zhaomin Lv; Xinwen Wang; Yian Zhou; Zipeng Qin; Lingfeng Guo; Lunyang Zhao (Computers and Geotechnics, 2025)

Sulfur vacancy-rich ZnIn2S4 via solvent engineering: Unveiling structure-defect-activity relationships for photocatalytic ranitidine degradation - Yilan Wang; Lingfeng Ouyang; Shuai Zhang; Zhanghong Zhou; Carolina Belver; Season Si Chen; Hao Wu (Chemical Engineering Journal, 2025)

An incoherent feed-forward loop coordinates nitrate uptake and tillering in wheat - Weiya Xu; Yongming Chen; Yanxiao Niu; Bin Liu; Dejie Du; Xining Ning; Tong Huan; Yilan Zhou; Wensheng Ke; Lingfeng Miao; Weilong Guo; Mingming Xin; et al. (Molecular Plant, 2025)

A data-driven multi-objective optimisation framework for energy efficiency and thermal comfort in flexible building spaces - Huanbo Lyu; Daniel Herring; Hongkuan Chen; Shiqiao Zhou; Jianyu Zhang; Lingfeng Wang; Zheming Zuo; James Andrews; Michal kočvara; Fabian Spill; Jelena Ninic; Shuo Wang (Energy and Buildings, 2025)

In situ electrocatalytic nitrate-to-nitrite conversion-driven anammox in MBRs for extremely efficient ammonium-containing wastewater treatment - Lingfeng Ni; Peifang Wang; Gang Zhou; Zibin Li; Yayi Wang (Water Research, 2025)

Comparative analysis of machine learning based dissolved oxygen predictions in the Yellow River Basin: The role of diverse environmental predictors - Lingling Liu; Xiaoli Zhao; Lingfeng Zhou; Jiangtao Liu; Wenjing Li; Bolun Zhang; Junhong Ling; Fengchang Wu (Journal of Environmental Management, 2025)

Nano-magnetoelectric biomimetic system promotes neural differentiation and reverses dopaminergic neuron damage for Parkinson's disease therapy - Jie Zhang; Jiahui Shi; Qiubo Yang; Haogang Guo; Lingfeng Guo; Guoliang Zhou; Yinyi Liu; Xiaolei Wang; Xian Hao; Yifei Yang (Chemical Engineering Journal, 2025)

Late Oligocene paleosols in the Haltang Basin of northeastern Tibetan Plateau and their implications for the early extent of the Asian monsoon - Zhaobin Zhang; Shuang Dai; Xinnan Fang; Xiaojun Ma; Yufan Zhang; Zhongzhao Ding; Lingfeng Qin; Chunyan Li; Meng Zhou; Tianqi Ji; Jie Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Targeting Nrf2 by bioactive peptides alleviate inflammation: expanding the role of gut microbiota and metabolites - Zhongxing Chu; Lingfeng Zhu; Yaping Zhou; Feiyan Yang; Zuomin Hu; Yi Luo; Wen Li; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2025)

Machine learning-based prediction of terrestrial heat-flow across mainland China - Chang Ni; Shan Xu; Xiangyun Hu; Xianchun Tang; Wenglong Zhou; Lingfeng Gao (Tectonophysics, 2025)

Bond durability between GFRP bars and seawater sea sand concrete in marine environments - Guanghao Mai; Zhe Xiong; Haoran Zhou; Lingfeng Zhou; Huanyu Zhu; Lijuan Li (Engineering Structures, 2025)

Advanced design of the crushing chamber for the sugarcane top silage cutter in harvester with experiments and simulation - Peng Huo; Shaochun Ma; Jun Qian; Weiqing Li; Baocheng Zhou; Wei Liu; Wenpeng Liang; Wenzhi Li; Changyu Wang; Sha Yang; Lingfeng Li; Yechen Li; et al. (Computers and Electronics in Agriculture, 2025)

The coupling of ultra-nano oxygenation and in-situ sediment remediation technology jointly promotes phosphorus enrichment and nitrogen removal - Lu Cao; Lingling Wan; Chunhui Xi; Zijun Zhou; Siyang Wang; Lingfeng Cao; Zhicheng Min; Xiankun Chen; Yiyong Zhou; Xiuyun Cao; Chunlei Song (Journal of Water Process Engineering, 2025)

Optimal balance of organic detritus and feed for fish growth and water quality improvement through regulating nutrients cycling - Lu Cao; Lingling Wan; Lingfeng Cao; Zhicheng Min; Yiyong Zhou; Xiuyun Cao; Chunlei Song (Environmental Research, 2024)

Targeting gut-brain axis by dietary flavonoids ameliorate aging-related cognition decline: Evidences and mechanisms - Zhongxing Chu; Shuai Han; Yi Luo; Yaping Zhou; Lingfeng Zhu; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2024)

Co-grown novel S-scheme tubular P–UCN/S-TCN homojunction mediates photocatalysis-PMS activation synergistic system for efficient degradation of antibiotic - Ting Wu; Zhifeng Liu; Binbin Shao; Yuan Pan; Qingyun He; Xiansheng Zhang; Lingfeng Zhou; Yunze Wang; Teng Li; Sheng Liu (Chemosphere, 2024)

Mapping critical soil moisture thresholds of water stress for global grasslands - Lingfeng Shi; Yanlian Zhou; Wei He; Zhoutong Dong; Zhuoyou Jiang; Yuyan Wang; Yibo Liu; Weimin Ju; Zheng Duan (Journal of Hydrology, 2024)

Paleoclimate evolution of the Middle Triassic Guanling Formation from South China and its significance for the preservation of the Luoping biota - Zhongzhao Ding; Zhixin Ma; Shixue Hu; Shuang Dai; Qiyue Zhang; Xiao Min; Jinyuan Huang; Wen Wen; Changyong Zhou; Xinnan Fang; Tianqi Ji; Lingfeng Qin (Global and Planetary Change, 2024)

Bioorthogonal surface-edited exosomes for targeted multimodal imaging and synergic chemophototherapy of oral cancer - Yuxiao Wu; Xiaofeng Shan; Yuanjie Zhang; Wen Shi; Xingxing Zhu; Mengfan Yu; Shang Xie; Lingfeng Guo; Zhiqian Chen; Chuanling Zhang; Demin Zhou; Zhigang Cai (Chemical Engineering Journal, 2024)

Characterization of piRNAs in Diploid and Triploid Pacific Oyster Gonads: Exploring Their Potential Roles in Triploid Sterility - Yaru Zhou; Hong Yu; Qi Li; Lingfeng Kong; Shikai Liu; Chengxun Xu (Marine Biotechnology, 2024)

Unveiling the structure-performance of MoO3/La2O2CO3 for ultra-deep aerobic oxidative desulfurization of diesel - Shijia Shao; Hui Liu; Xiangdong Wang; Lingfeng Jia; Shuhui Zhou; Yan Huang; Huifang Cheng; Feng Liu; Yun Wang; Jixing Liu; Wenshuai Zhu (Chemical Engineering Journal, 2024)

Ball milling nano-sized biochar: bibliometrics, preparation, and environmental application - Lingfeng Zeng; Jiezhi Ma; Jie Yang; Jian Yang; Xiangzhou Zeng; Yaoyu Zhou (Environmental Science and Pollution Research, 2024)

Recent advances on environmental behavior of Cu-based nanomaterials in soil-plant system: A review - Jieyu Gao; Yi Zhu; Lingfeng Zeng; Xin Liu; Yuan Yang; Yaoyu Zhou (Journal of Environmental Management, 2024)

Relationship between eutrophication and greenhouse gases emission in shallow freshwater lakes - Jingjie Zhang; Lingfeng Cao; Zhenghan Liu; Lingling Wan; Xiuyun Cao; Yiyong Zhou; Chunlei Song (Science of The Total Environment, 2024)

Current progress on manganese in constructed wetlands: Bibliometrics, effects on wastewater treatment, and plant uptake - Lingfeng Zeng; Xin Liu; Jiezhi Ma; Jie Yang; Jian Yang; Yaoyu Zhou (Environmental Research, 2024)

Nanofiltration membrane with modified nano-gradient structure and positive charge for Li separation from high Mg/Li ratio brine - Peng Zhao; Fei Guo; Lingfeng Wang; Huange Zhen; Ning Zhang; Shaohua Yin; Guoli Zhou; Xuehua Ruan; Gaohong He; Xiaobin Jiang (Desalination, 2024)

Differences in the activities of six soil enzymes in response to cadmium contamination of paddy soils in high geological background areas - Juan Liu; Xinyang Li; Qilin Zhu; Jiawen Zhou; Lingfeng Shi; Weihong Lu; Li Bao; Lei Meng; Longhua Wu; Naiming Zhang; Peter Christie (Environmental Pollution, 2024)

Development of novel single fuel cell based on composite polar plates for highly efficient power generation - Caiying Zhou; Yancheng Wang; Deqing Mei; Wenze Mao; Lingfeng Xuan (Fuel, 2024)

MOF derived MnFeOX supported on carbon cloth as electrochemical anode for peroxymonosulfate electro-activation and persistent organic pollutants degradation - Xiansheng Zhang; Yuan Pan; Yunze Wang; Ting Wu; Binbin Shao; Qingyun He; Lingfeng Zhou; Teng Li; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

Application of 3D hierarchical porous NiCo-spinel nanosheet array for enhancement of synergistic activation of peroxymonosulfate: Degradation, Intermediates, mechanism and degradation pathway of tetracycline - Yuan Pan; Xiansheng Zhang; Ting Wu; Binbin Shao; Teng Li; Qingyun He; Zehua Chen; Lingfeng Zhou; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

An integrated analysis of the fecal metabolome and metagenome reveals the distinct effects of differentially charged nanoplastics on the gut microbiota-associated metabolites in mice - Miaomiao Teng; Xiaoli Zhao; Lingfeng Zhou; Hong Yan; Lihui Zhao; Jiaqi Sun; Yunxia Li; Wentao Zhu; Fengchang Wu (Science of The Total Environment, 2024)

Overlooked fluorine deficiency in children of South and East China may be exacerbated by climate change: Evidence from the national assessment - Lingfeng Zhou; Weigang Liang; Yaobin Meng; Xiaoli Zhao; Fei Guo; Lingling Liu; Wenjing Li; Miaomiao Teng; Fanhao Song; Zhiqiang Cao; Yidong Mi; Qigen Lin; et al. (Journal of Cleaner Production, 2024)

An improved numerical manifold method for crack propagation of concrete gravity dams under seismic loads - Yujie Xu; Yuan Wang; Lingfeng Zhou; Qi Dong (Computers and Geotechnics, 2024)

Interfacial electronic engineering of heterostructured Co2P-MoNiP/NF nano-sea-urchin catalysts for efficient and stable hydrogen evolution via water/seawater splitting - Yifan Zhao; Hua Zhang; Ji Chen; Shuwen Zhao; Min Xi; Lingfeng Yang; Youyu Long; Zitao Ni; Yao Zhou; Anran Chen (Chemical Engineering Journal, 2023)

Molecular-level insights into the heterogeneous variations and dynamic formation mechanism of leached dissolved organic matter during the photoaging of polystyrene microplastics - Fanhao Song; Tingting Li; Jin Hur; Quan Shi; Fengchang Wu; Wei He; Di Shi; Chen He; Lingfeng Zhou; Mingqi Ruan; Yuhan Cao (Water Research, 2023)

Model-based evaluation of reduction strategies for point and nonpoint source Cd pollution in a large river system - Lingfeng Zhou; Xiaoli Zhao; Miaomiao Teng; Fengchang Wu; Yaobin Meng; Yating Wu; Patrick Byrne; Karim C. Abbaspour (Journal of Hydrology, 2023)

Modeling transport and fate of heavy metals at the watershed scale: State-of-the-art and future directions - Lingfeng Zhou; Fengchang Wu; Yaobin Meng; Patrick Byrne; Mory Ghomshei; Karim C. Abbaspour (Science of The Total Environment, 2023)

Integrated assessment of land-to-river Cd fluxes and riverine Cd loads using SWAT-HM to guide management strategies - Lingfeng Zhou; Miaomiao Teng; Fanhao Song; Xiaoli Zhao; Fengchang Wu; Yaobin Meng; Yuanyi Huang; Karim C. Abbaspour (Journal of Environmental Management, 2023)

Sugarcane leaf-stalk separating technology: A critical review - Peng Huo; Shaochun Ma; Chenyang Su; Zhengliang Ding; Weiqing Li; Jun Qian; Lingfeng Li; Yechen Li; Baocheng Zhou; Chong Peng; Wenzhi Li (Biosystems Engineering, 2023)

Surface display of major capsid protein on Bacillus subtilis spores against largemouth bass virus (LMBV) for oral administration - Quan Wang; Xia Liang; Yunshang Ning; Shijia Liu; Zengjian Liang; Zemiao Zhang; Yingjing Chen; Jinqiao Cao; Fubao Wang; Lingfeng Lan; Guangzhao Cheng; Youhua Huang; et al. (Fish & Shellfish Immunology, 2023)

Transcriptome Analysis of Reciprocal Hybrids Between Crassostrea gigas and C. angulata Reveals the Potential Mechanisms Underlying Thermo-Resistant Heterosis - Gaowei Jiang; Yin Li; Geng Cheng; Kunyin Jiang; Jianmin Zhou; Chengxun Xu; Lingfeng Kong; Hong Yu; Shikai Liu; Qi Li (Marine Biotechnology, 2023)

Metagenomic insights into feasibility of agricultural wastes on optimizing water quality and natural bait by regulating microbial loop - Lingling Wan; Lingfeng Cao; Chunlei Song; Xiuyun Cao; Yiyong Zhou (Environmental Research, 2023)

Experimental investigation and decoupling of voltage losses distribution in proton exchange membrane fuel cells with a large active area - Zihan Zhou; Lingfeng Ye; Diankai Qiu; Linfa Peng; Xinmin Lai (Chemical Engineering Journal, 2023)

Combined toxicity of chlorpyrifos, abamectin, imidacloprid, and acetamiprid on earthworms (Eisenia fetida) - Miaomiao Teng; Xiaoli Zhao; Chen Wang; Lingfeng Zhou; Xiaowei Wu; Fengchang Wu (Environmental Science and Pollution Research, 2022)

Effect of Angiogenesis in Bone Tissue Engineering - Jianhao Huang; Qixiu Han; Meng Cai; Jie Zhu; Lan Li; Lingfeng Yu; Zhen Wang; Gentao Fan; Yan Zhu; Jingwei Lu; Guangxin Zhou (Annals of Biomedical Engineering, 2022)

Ecosystem Services of Ecosystem Approach to Mariculture: Providing an Unprecedented Opportunity for the Reform of China’s Sustainable Aquaculture - Xijie Zhou; Jinghui Fang; Siyuan Shi; Ling Yang; Bin Xie; Lingfeng Huang (Frontiers in Marine Science, 2022)
China is the biggest provider of mariculture products, and the industry is still growing rapidly. Increasing scientific evidence indicates that mariculture may provide valuable ecosystem goods and services in China. Here, we performed a systematic literature review of studies with the aim of understanding the ecosystem services of mariculture and a comprehensive review of ecosystem approaches that may improve mariculture ecosystem services and goods in China. We highlight four ecosystem services functions in China, including food supply, nutrient extraction, carbon sequestration, and biodiversity conservation. Given the further reform of China’s mariculture, we outlined several ecosystem approaches including integrated multi-trophic aquaculture (IMTA), carrying capacity assessment and monitoring, marine spatial planning, and waste treatment and recirculating mariculture system. We conclude that the ecosystem services of the ecosystem approach to mariculture provide an unprecedented opportunity for the reform of China’s sustainable aquaculture. Finally, a synthesis of sustainable development of mariculture, along with the five recommendations for future mariculture development in China, is outlined.

Review of construction methods for whole-cell computational models - Jingru Zhou; Xingcun Fan; Lingfeng Cao; Huijie Sun; Jianye Xia; XueFeng Yan (Systems Microbiology and Biomanufacturing, 2022)

The geographic and climatic distribution of plant height diversity for 19,000 angiosperms in China - Lingfeng Mao; Nathan G. Swenson; Xinghua Sui; Jinlong Zhang; Shengbin Chen; Jingji Li; Peihao Peng; Guangsheng Zhou; Xinshi Zhang (Biodiversity and Conservation, 2020)

Initial results of centralized autonomous orbit determination of the new-generation BDS satellites with inter-satellite link measurements - Chengpan Tang; Xiaogong Hu; Shanshi Zhou; Li Liu; Junyang Pan; Liucheng Chen; Rui Guo; Lingfeng Zhu; Guangming Hu; Xiaojie Li; Feng He; Zhiqiao Chang (Journal of Geodesy, 2018)

Performance of the BDS3 experimental satellite passive hydrogen maser - Ziqian Wu; Shanshi Zhou; Xiaogong Hu; Li Liu; Tao Shuai; Yonghui Xie; Chengpan Tang; Junyang Pan; Lingfeng Zhu; Zhiqiao Chang (GPS Solutions, 2018)

QSAR modeling and in silico design of small-molecule inhibitors targeting the interaction between E3 ligase VHL and HIF-1 $$α $$ α - Jing Pan; Yanmin Zhang; Ting Ran; Anyang Xu; Xin Qiao; Lingfeng Yin; Weineng Zhou; Lu Zhu; Junnan Zhao; Tao Lu; Yadong Chen; Yulei Jiang (Molecular Diversity, 2017)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Spatial patterns and environmental correlates of bryophyte richness: sampling effort matters - Shengbin Chen; J. W. Ferry Slik; Lingfeng Mao; Jian Zhang; Rula Sa; Kexin Zhou; Jixi Gao (Biodiversity and Conservation, 2015)

Environmental determinants of geographic butterfly richness pattern in eastern China - Shengbin Chen; Lingfeng Mao; Jinlong Zhang; Kexin Zhou; Jixi Gao (Biodiversity and Conservation, 2014)